2005
DOI: 10.1016/j.amjhyper.2005.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Masked Hypertension Assessed by Ambulatory Blood Pressure Versus Home Blood Pressure Monitoring: Is It the Same Phenomenon?

Abstract: Similar proportions of subjects with masked hypertension are detected by ABP and HBP monitoring. Although disagreement in the diagnosis between the two methods is not uncommon, in the majority of these cases the deviation of the diagnostic BP above the threshold in not clinically important. Both ABP and HBP monitoring appear to be appropriate methods for the detection of masked hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
97
0
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(116 citation statements)
references
References 19 publications
8
97
0
11
Order By: Relevance
“…1 In line with other reports, 12,15 when home BP was used to diagnose MH, there was disagreement with the ambulatory BP diagnosis in 22%. This disagreement is probably due, at least in part, to random variation above and below the BP threshold, 15 and supports the view that home and ambulatory BP are interchangeable methods in the diagnosis of MH. 15 Similar proportions of subjects with MH are detected by ABP and HBP monitoring.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…1 In line with other reports, 12,15 when home BP was used to diagnose MH, there was disagreement with the ambulatory BP diagnosis in 22%. This disagreement is probably due, at least in part, to random variation above and below the BP threshold, 15 and supports the view that home and ambulatory BP are interchangeable methods in the diagnosis of MH. 15 Similar proportions of subjects with MH are detected by ABP and HBP monitoring.…”
Section: Discussionmentioning
confidence: 61%
“…This disagreement is probably due, at least in part, to random variation above and below the BP threshold, 15 and supports the view that home and ambulatory BP are interchangeable methods in the diagnosis of MH. 15 Similar proportions of subjects with MH are detected by ABP and HBP monitoring. Although disagreement in the diagnosis between the two methods is not uncommon, in the majority of these cases, the deviation of the diagnostic BP above the threshold in not clinically important.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Although the CHEP Recommendations Task Force recognized that additional evidence is required before recommendations regarding diagnosis and management of masked hypertension can be developed, the compelling evidence from the SHEAF study regarding the clinical implications of masked hypertension resulted in the new recommendation for 2006 that continued home/self BP monitoring be considered for treated hypertensive patients with BP controlled in the office but not at home (masked hypertension). The use of ABPM has also been used in the assessment of masked hypertension (30), and will be discussed in upcoming iterations of the CHEP guidelines as evidence from ongoing studies becomes available. The CHEP Recommendations Task Force felt it important to emphasize that adequate patient training is required to ensure accurate BP results from home/self BP monitoring.…”
Section: Reproduced With Permission From the Canadian Hypertension Edmentioning
confidence: 99%
“…9 While ABPM and HBPM were each associated with outcomes, the authors concluded that there was insufficient evidence to consider either modality to be superior. Further, a study by Stergiou et al 10 found substantial disagreement between ABPM and HBPM when used to identify masked hypertension. Only 44% of participants had masked hypertension on both modalities.…”
mentioning
confidence: 99%